Phase I Clinical Trial of an Autologous Dendritic Cell Vaccine Against HER2 Shows Safety and Preliminary Clinical Efficacy - Maeng, Hoyoung M.; Moore, Brittni N.; Bagheri, Hadi; Steinberg, Seth M.; Inglefield, Jon; Dunham, Kim; Wei, Wei-Zen; Morris, John C.; Terabe, Masaki; England, Lee C.; Roberson, Brenda; Rosing, Douglas; et al. (Frontiers in Oncology, 2021)
Background Despite recent advances, there is an urgent need for agents targeting HER2-expressing cancers other than breast cancer. We report a phase I study (NCT01730118) of a dendritic cell (DC) vaccine targeting HER2 in patients with metastatic cancer or bladder cancer at high risk of relapse. Patients and Methods Part 1 of the study enrolled patients with HER2-expressing metastatic cancer that had progressed after at least standard treatment and patients who underwent definitive treatment for invasive bladder cancer with no evidence of disease at the time of enrollment. Part 2 enrolled patients with HER2-expressing metastatic cancer who had progressed after anti-HER2 therapy. The DC vaccines were prepared from autologous monocytes and transduced with an adenoviral vector expressing the extracellular and transmembrane domains of HER2 (AdHER2). A total of five doses were planned, and adverse events were recorded in patients who received at least one dose. Objective response was evaluated by unidimensional immune-related response criteria every 8 weeks in patients who received at least two doses. Humoral and cellular immunogenicity were assessed in patients who received more than three doses. Results A total of 33 patients were enrolled at four dose levels (5 × 106, 10 × 106, 20 × 106, and 40 × 106 DCs). Median follow-up duration was 36 weeks (4–124); 10 patients completed five doses. The main reason for going off-study was disease progression. The main adverse events attributable to the vaccine were injection-site reactions. No cardiac toxicity was noted. Seven of 21 evaluable patients (33.3%) demonstrated clinical benefit (1 complete response, 1 partial response, and 5 stable disease). After ≥3 doses, an antibody response was detected in 3 of 13 patients (23.1%), including patients with complete and partial responses. Lymphocytes from 10 of 11 patients (90.9%) showed induction of anti-HER2 responses measured by the production of at least one of interferon-gamma, granzyme B, or tumor necrosis factor-alpha, and there were multifunctional responses in 8 of 11 patients (72.7%). Conclusions The AdHER2 DC vaccine showed evidence of immunogenicity and preliminary clinical benefit in patients with HER2-expressing cancers, along with an excellent safety profile. It shows promise for further clinical applications, especially in combination regimens.